Improving the Speaking Ability at the Second Grade Students of SMKN 1 Watunohu Through Media Picture - Muhammad Afif (USN Scientific Journal, 2022)
This research was aimed to improved of students’ ability in speaking ability through media picture. The subject of this research was 25 students of the second grade students of SMKN 1 Watunohu . The researcher applied classroom action research which has conducted into two cycles. The finding showed that the students’ speaking ability indicated the significant increase from the average score of speaking ability within the two cycles (cycle 1 and 2). In average score of test, the achievement score was 55,4 for cycle 1 and 77,6 for cycle 2. From these results, this research indicated that media picture can improve the students’ speaking ability in teaching and learning process, particularly on the aspect of introducing someone, retell profill of the picture and explain someone based on the prifile of the picture.